PRAKTEK EKONOMI ISLAM UMAR BIN KHATAB SEBAGAI KEPALA NEGARA - Muhammad Baiquni Syihab; Yuana Tri Utomo (Program Studi Akuntansi IKOPIN, 2022)
This study seeks to trace the foundations of Umar bin Khatab's power and policies in the economic field. This research is qualitative, literature study, and uses a historical approach. The results of this study indicate that the economic policy implemented by Umar bin Khattab is an economic policy that comes from sources of Islamic law, namely the Qur'an and the Hadith of the Prophet Muhammad. That Umar bin Khattab prohibited usury in his country, collected zakat and jizya from his people and redistributed them to his people according to Islamic law with the consideration of his leadership. Umar bin Khattab's policies are coercive in the sense that they are rules, and not mere appeals or calls.